Digital Innovation as a Driver of Change in the Government Procurement System in the 5.0 Era - Kalupe, Sultan; Tahir, Arifin; Amir Arham, Muhammad; Aneta, Yanti (Iapa Proceedings Conference, 2024)
Digital transformation in the era of the industrial revolution 4.0 and society 5.0 provides opportunities for the public sector, including in the procurement of government goods/services, to increase efficiency, transparency, and accountability. This study aims to analyze the implementation of digital transformation in the procurement of goods/services in Gorontalo Province through e-catalogues and online stores (e-purchasing). Research data was collected through in-depth interview methods, observations, and analysis of documents related to procurement transactions. The results of the study show that procurement digitalization has increased the involvement of local MSMEs and minimized the potential for misappropriation. However, there are a number of technical obstacles that affect the smooth implementation, such as the lack of readiness of human resources (HR) and the limitations of integration between digital platforms. To optimize the results of this transformation, more intensive human resource training and improvement of supporting technology infrastructure are needed. Thus, the digital transformation of procurement of goods/services in Gorontalo has the potential to become a more transparent and efficient procurement governance model in the future.